a, [TEX](x-2)y=-5=1.(-5)=5.(-1)[/TEX].
Nếu [TEX]x-2=1 \Rightarrow x=3[/TEX] và [TEX]y=-5[/TEX].
Nếu [TEX]x-2=-1 \Rightarrow x=1[/TEX] và [TEX]y=5[/TEX].
Nếu [TEX]x-2=5 \Rightarrow x=7[/TEX] và [TEX]y=-1[/TEX].
Nếu [TEX]x-2=-5 \Rightarrow x=-3[/TEX] và [TEX]y=1[/TEX].
Như vậy ta có 4 đáp án.
b, Tương tự
c, [TEX]x(y-1)-y=2 \Rightarrow x(y-1)-y+1=3 \Rightarrow x(y-1)-(y-1)=3 \Rightarrow (x-1)(y-1)=3[/TEX].
Đến đây áp dụng cách như câu a.
d, [TEX]x(y-2) = 2.y +3 \Leftrightarrow x(y-2)-2y=3 \Leftrightarrow x(y-2)-2y+4=7 \Leftrightarrow x(y-2)-2(y-2)=7 \Leftrightarrow (x-2)(y-2)=7[/TEX].
e, [TEX]x.y + x + y = 0 \Leftrightarrow x(y+1)+y=0 \Leftrightarrow x(y+1)+(y+1)=1 \Leftrightarrow (x+1)(y+1)=1[/TEX].
f, [TEX]x.y - 2.x - 3.y = 2 \Leftrightarrow x(y-2)-3y+6=8 \Leftrightarrow x(y-2)-3(y-2)=8 \Leftrightarrow (x-3)(y-2)=8[/TEX]
g, [TEX]\frac{1}{x} + \frac{1}{y} = \frac{1}{2}[/TEX]
[TEX]\Leftrightarrow \frac{x+y}{xy}= \frac{1}{2} \Leftrightarrow 2(x+y)=xy[/TEX]
[TEX]\Leftrightarrow 2x+2y-xy=0 \Leftrightarrow x(2-y)+2y=0[/TEX]
[TEX]\Leftrightarrow x(2-y)+2y-4=-4 \Leftrightarrow x(2-y)-2(2-y)=-4[/TEX]
[TEX]\Leftrightarrow (x-2)(2-y)=-4[/TEX].